"If Geert Wilders Has Freedom of Speech, We Have Freedom of Speech!": Girls' Soccer, Race, and Embodied Knowledge in/of the Netherlands. Issue 1 (29th April 2021) - van den Bogert, Kathrine
Abstract: This article discusses the role of race as it intersects with religion, gender, and class in Dutch public spaces through an ethnography of Moroccan‐Dutch Muslim girls playing soccer. Racialized Muslim girls are "othered" and portrayed as unemancipated and inactive in Dutch society, not in the least by politicians such as Geert Wilders. Yet, racialized girls resist their "othering" by appropriating public sports spaces for their own girls' soccer competition. I show how soccer players deal with racist comments in sports and how they respond to right‐wing nationalism and racist populism by playing soccer. I argue that the girls' embodied knowledge of such experiences is crucial for scholarly understandings of race, racialization, public space, and sports. This article demonstrates how race works in Dutch public sports spaces, and how gender, religion, and class are produced through racialization in sports.